Profile of Broiler Chicken Farmers and Supporting Resources in Kepulauan Yapen Regency, Papua Province - Supriyantono, Andoyo; Mulyadi; W. Widayati, Trisiwi; M. Karubaba, Soleman (Jurnal Agrosci, 2024)
Efforts to realize chicken meat consumption have not been achieved. Broiler chicken production in Kepulauan Yapen was about 7,379 and it was not comparable to the human population of 112,676 people. The per capita consumption of chicken meat in Kepulauan Yapen is still far from the national consumption of broiler chicken meat. The research uses descriptive methods with case study techniques. Data taken includes gender, age, education level, business scale, number of family members, farming experience, main job, and marketing channel. Data was obtained from farmers using questionnaires and from various related agencies of the Kepulauan Yapen. The collected data was analyzed using Minitab version 17 to obtain the average and percentage of each data obtained. Results of research showed that the majority of farmers who raise broiler chickens are male (81.82%), aged 15-65 years (100%), have a diploma or above education (45.5%), the scale of business is micro (100%), the number of family members involved in raising broiler chickens is 4 – 6 (54.5%), the farming experience is less than 10 years (100%), the main occupation is others such as trading, hunting (45.45%) and the marketing channel is from farmers directly to consumers.